THE ISOELECTRIC POINT OF RED BLOOD CELLS AND ITS RELATION TO AGGLUTINATION - Coulter, Calvin B. (The Rockefeller University Press, 1921)
1. The movement of normal and sensitized red blood cells in the electric field is a function of the hydrogen ion concentration. The isoelectric point, at which no movement occurs, corresponds with pH 4.6. 2. On the alkaline side of the isoelectric point the charge carried is negative and increases with the alkalinity. On the acid side the charge is positive and increases with the acidity. 3. On the alkaline side at least the charge carried by sensitized cells is smaller and increases less rapidly with the alkalinity than the charge of normal cells. 4. Both normal and sensitized cells combine chemically with inorganic ions, and the isoelectric point is a turning point for this chemical behavior. On the acid side the cells combine with the hydrogen and chlorine ions, and in much larger amount than on the alkaline side; on the alkaline side the cells combine with a cation (Ba), and in larger amount than on the acid side. This behavior corresponds with that found by Loeb for gelatin. 5. The optimum for agglutination of normal cells is at pH 4.75, so that at this point the cells exist most nearly pure, or least combined with anion and cation. 6. The optimum for agglutination of sensitized cells is at pH 5.3. This point is probably connected with the optimum for flocculation of the immune serum body.